ETHNOGRAPHY OF THE SYARAHWANDAN TRADITION (Study of the Values of Islamic Education) - Umarella, Samad; Lasaiba, Irvan (al-Iltizam: Jurnal Pendidikan Agama Islam, 2022)
To achieve the educational objectives, then various approaches are used. One of the approaches is cultural approach. Such as Syarahwandan culture in Wandan society (Banda ely). This culture contains many islamic educational values, then to express the values of Islamic education contained in it, the researcher uses the theory of ethnography with qualitative descriptive method to reveal how the implementation of syarahwandan and the values of Islamic education contained in it. In this study, the researcher found that syarahwandan culture contains aqidah educational values, syari'ah educational values and akhlaq (moral) educational values, so then Syarahwandan culture can be used as a media of modern education for the wandan society (Banda Ely)